Asosiasi Pengetahuan Mengenai Rokok dengan Sikap dan Perilaku Merokok pada Remaja - ROCHIMA RIDHA HIDAYAH; ARI NATALIA PROBANDARI; MUTHMAINAH . (Nexus Kedokteran Komunitas, 2012)
Background: The level of knowledge on smoking may influences the attitudes and behavior of smoking. A previous research found that, smoking behavior began in the early years of teenage (11-15 years old). This study aimed to determine the association between the level of knowledge about the dangers of smoking cigarettes and attitudes toward smoking and smoking behavior in early adolescence. Methods: The study design was an observational analytic cross-sectional study which was conducted during March 2012 among 98 students of SMP Negeri 01 Colomadu, Karanganyar. Sampling technique in this study was multi-stage cluster sampling. We used a questionnaire to measure current knowledge on smoking and the dangers of smoking, attitudes, and smoking behavior, which had been tested validity and reliability. Data analysis used the Fisher Exact Test and Chi-Square Test. Results: This study found no statistical significant relationship between the level of knowledge of the attitudes toward smoking (p = 0,509; OR = 1,86; Cl95% = 0,45-7,66). The level of knowledge increased the risk of smoking behavior in the past by 0,7 times (p = 0,366; OR = 1,50; Cl95% = 0,62-3,62), but not statistical significantly. There were no statistical significant relationship between the level of knowledge of the behavior of current smoking (p = 0,311; OR = 4,23; Cl95% = 0,42-42,20) and past smoking (p = 0,366; OR = 1,50; Cl95% = 0,62-3,62). Conclusions: The knowledge has no statistical significant association with adolescent attitudes toward smoking and smoking behavior of adolescents. Further research with stronger study designs are needed to study the association between knowledge, attitude on smoking and smoking behavior among early teenagers. Keywords: Level of knowledge challenged cigarettes, attitudes, smoking behavior.